Carotid intraplaque neovascularization increases the risk of white matter hyperintensity progression: a prospective cohort study - Zhang, Hao; He, Jun; Xu, Jimei; Wang, Rongfeng; Yan, Yan; Feng, Yuan; Cao, Shugang; Xia, Mingwu (Frontiers in Neuroscience, 2026)
Background and purposeWhite matter hyperintensities (WMH) are a common imaging manifestation of cerebral small vessel disease (CSVD). While carotid intraplaque neovascularization (IPN) has been implicated in WMH burden, its longitudinal impact on WMH progression, particularly across different brain regions, remains to be fully elucidated.MethodsWe conducted a longitudinal cohort study of patients with baseline WMH, who underwent carotid IPN grading (Grade 0–2) via AngioPLUS ultrasound. Clinical demographics, vascular risk factors, and key laboratory parameters (including homocysteine and LDL-C) were collected. WMH progression was defined as an increase in the total score of the visual Rotterdam Progression Scale (range: −7 to +7) by ≥1 point on follow-up MRI, indicating new or enlarged lesions. Logistic regression analysis was used to determine the relationship between IPN and progression of white matter hyperintensities.ResultsIn this longitudinal cohort study, a total of 213 patients (mean age 71.0 ± 8.9 years; 56.8% male) were included in the final analysis. Over a mean follow-up period of 17.8 months (range: 4–52 months), overall progression of white matter hyperintensities (WMH) was observed in 124 patients (58.2%). Specifically, progression of periventricular WMH (PWMH) and deep WMH (DWMH) occurred in 42.3 and 33.8% of patients, respectively. Patients with WMH progression showed a significantly higher prevalence of vascular risk factors compared to those without progression. Logistic regression analysis, after adjustment for age, smoking, alcohol consumption, hypertension, diabetes, history of stroke, body mass index, low-density lipoprotein cholesterol, and follow-up duration, indicated that grade 2 (high-grade) intraplaque neovascularization in the carotid artery was independently associated with the progression of deep white matter hyperintensities (OR 2.06, 95% CI 1.05–4.05).ConclusionCarotid intraplaque neovascularization is an independent predictor of deep WMH progression. Assessing plaque vulnerability via IPN grading may help identify patients at high risk for progressive white matter injury and serve as a potential target for therapeutic intervention.